A construção do ator “garimpeiro” em “Ouro, Serra Pelada, Brasil”, de Sebastião Salgado - Lopes, Gustavo Henrique Gyrão de Paula (2014)
This research proposes the analysis of a syncretic text, selected photographs of "Ouro, Serra Pelada, Brasil" series, from the book "Trabalhadores – uma arqueologia da era industrial", of photographer Sebastião Salgado, and verbal texts that accompany them. The theoretical assumptions are those of the french Semiotics. Initially, we applied to text elements of the generative process. Interests us, especially checking the discursive level, including the procedures used by the subject of the enunciation to constitute his discourse at the level of the figures of the actors, the space and time projected in the statement text and meaning effects that the mechanisms of projection chosen manufacture in the text. Salgado, while enunciating, is one of the greatest exponents of the so called documentary photography, and therefore his photographic discourse seems to present as factual as possible, creating therefore the effect of sense of objectivity. We are interested in understanding how the subject of enunciation can at the same time express figures that cover themes which remind us of social values, revealing a passionate enunciator, insofar in which the illusion of objectivity is deconstructed. We also aimed to infer the specific text Salgado as poetic text through it graspable semisymbolic relations. We intend, therefore, to understand how the categories of the sensible, the plane of expression (topological categories, chromatic and eidetic), correlate with the categories of the intelligible, the plan of the text content. The analysis allowed us to understand the miner as a subject moved by passion, motivated by obstinacy, that in his search for the object of value gold has the illusion of being master of his destiny. An actor who is sometimes presented covered by the theme of Christian suffering. Palavras-chave: Photography; syncretic text; actor; generative process; semisymbolism.